Numerical Study on Confinement Effect and Efficiency of Concentrically Loaded RACFRST Stub Columns - Liu, Yicen; Lyu, Fei; Ding, Faxing; Wang, En; Xu, Yunlong; Yuan, Tao; Deng, Chao; Luo, Chen (Frontiers in Materials, 2021)
The mechanical behaviours of recycled aggregate concrete (RAC) are upgraded by outer steel tube confinement, and the performance of recycled aggregate concrete-filled steel tubular (RACFST) columns is similar to that of the traditional concrete-filled steel tube (CFST) columns. The purpose of this study is to investigate the behaviours of recycled aggregate concrete-filled rectangular steel tubular (RACFRST) stub columns under axial loading. Three-dimensional finite element (FE) models were established, which utilized a triaxial plastic-damage constitutive RAC model considering the replacement ratio of recycled aggregates. The finite element analysis results indicated that the lessened ultimate bearing capacity of RACFRST stub columns compared with their traditional concrete infilled counterparts was mainly due to the weakened confinement effect and confinement efficiency. A simplified formula of the bearing capacity of concentrically loaded RACFRST stub columns was proposed. The cross-sectional stress nephogram was reasonably simpliﬁed by the limited state of infilled concrete. The basics of proposed formula were the equilibrium condition and the superposition method. Finally, the formula for the bearing capacity of RACFRST stub columns was evaluated by comparing its accuracy and feasibility to some design formulae proposed by specialists and some design codes of different regions.